A preliminary study of the incorparation of NPK fertilizer into chitosan nanoparticles (eXPRESS Polymer Letters, 2010)
The use of slow release fertilizer has become a new trend to save fertilizer consumption and to minimize environmental pollution. Due to its polymeric cationic, biodegradable, bioabsorbable, and bactericidal characteristics, chitosan (CS) nanoparticle is an interesting material for use in controlled release systems. However, there are no attempts to explore the potential of chitosan nanoparticles as controlled release for NPK fertilizers. In this work chitosan nanoparticles were obtained by polymerizing methacrylic acid for the incorporation of NPK fertilizers. The interaction and stability of chitosan nanoparticle suspensions containing nitrogen (N), phosphorus (P) and potassium (K) were evaluated by FTIR spectroscopy, particle size analysis and zeta-potential. The FTIR results indicated the existence of electrostatic interactions between chitosan nanoparticles and the elements N, P and K. The stability of the CS-PMAA colloidal suspension was higher with the addition of nitrogen and potassium than with the addition of phosphorus, due to the higher anion charge from the calcium phosphate than the anion charges from the potassium chloride and urea. The mean diameter increase of the CS-PMAA nanoparticles in suspension with the addition of different compounds indicated that the elements are being aggregated on the surface of the chitosan nanoparticles.